2022
DOI: 10.1124/molpharm.122.000543
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic α-Conotoxin Binding Site on the Human GABAB Receptor

Abstract: The analgesic α-conotoxins Vc1.1, RgIA, and PeIA attenuate nociceptive transmission via activation of G protein-coupled GABA B receptors (GABA B R) to modulate N-type calcium channels in primary afferent neurons and recombinantly co-expressed human GABA B R and Cav2.2 channels in HEK293T cells. Here, we investigated the effects of analgesic αconotoxins following the mutation of amino acid residues in the Venus Flytrap (VFT) domains of the GABA B R subunits predicted through computational peptide docking and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Previous studies demonstrated that the VFT region of the GABA B R1 subunit is typically where agonists and antagonists interact with the GABA B R, whereas some positive allosteric modulators are reported to interact at the pore region of the transmembrane domain . However, the binding site of conotoxins on the GABA B R has not been precisely determined. , Until recently, the binding site for several α-conotoxins was determined based on docking and mutagenesis studies . Docking calculations predicted that α-conotoxins form close contacts with VFT residues in both B1 and B2 subunits, which comprise a novel GABA B R ligand-binding site .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the VFT region of the GABA B R1 subunit is typically where agonists and antagonists interact with the GABA B R, whereas some positive allosteric modulators are reported to interact at the pore region of the transmembrane domain . However, the binding site of conotoxins on the GABA B R has not been precisely determined. , Until recently, the binding site for several α-conotoxins was determined based on docking and mutagenesis studies . Docking calculations predicted that α-conotoxins form close contacts with VFT residues in both B1 and B2 subunits, which comprise a novel GABA B R ligand-binding site .…”
Section: Discussionmentioning
confidence: 99%
“…15,21 Until recently, the binding site for several α-conotoxins was determined based on docking and mutagenesis studies. 41 Docking calculations predicted that α-conotoxins form close contacts with VFT residues in both B1 and B2 subunits, which comprise a novel GABA B R ligand-binding site. 40 GeX-2 could bind to a variety of positions at GABA B R according to peptide docking and results from clustering of the docked conformations suggested preferential interactions with the Nterminal or the VTF region of the R2 subunit.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…43 More recently, the binding of Vc1.1 to the GABA B R was investigated by a combination of molecular docking and molecular dynamics (MD) simulations, alongside confirmatory mutagenesis, electrophysiology and immunocytochemistry. 60 That study reported that Vc1.1 interacts directly with both B1 and B2 subunits of the GABA B R , in particular residues S130 and S131 in B1, and K168 in B2. The study also demonstrated 60 The development of Vc1.1 and its analogues originally primarily focused on systemic delivery through intramuscular administration for neuropathic pain.…”
Section: Pharmacology At the Gaba B Receptormentioning
confidence: 94%
“…60 That study reported that Vc1.1 interacts directly with both B1 and B2 subunits of the GABA B R , in particular residues S130 and S131 in B1, and K168 in B2. The study also demonstrated 60 The development of Vc1.1 and its analogues originally primarily focused on systemic delivery through intramuscular administration for neuropathic pain. In 2017, a potentially new application for chronic visceral pain was proposed following the response observed for Vc1.1 in an ex vivo assay for chronic visceral hypersensitivity (CVH) when compared with established GABA B agonists.…”
Section: Pharmacology At the Gaba B Receptormentioning
confidence: 94%
“…Cone snail venoms are a particularly rich source of peptides that target ion channels as well as other receptors (Bony et al, 2022;Liang et al, 2022;Ruelas-Callejas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%